Transcranial Magnetic Stimulation in the Diagnosis of Cervical Compressive Myelopathy. Issue 3 (1st February 2015) - Funaba, Masahiro; Kanchiku, Tsukasa; Imajo, Yasuaki; Suzuki, Hidenori; Yoshida, Yuichiro; Nishida, Norihiro; Taguchi, Toshihiko
<x xml:space="preserve">Abstract</x> Study Design. Single-center retrospective study. Objective. To reveal the characteristic changes in central motor conduction time (CMCT) produced by transcranial magnetic stimulation among the responsible levels of cervical compressive myelopathy (CCM). Summary of Background Data. CMCT is a useful and noninvasive measure for evaluating the central motor pathway. However, a systematic correlation between CMCT findings and the responsible level of CCM has so far not been addressed in a large patient cohort. Method. We measured CMCT in 75 patients with CCM who were determined by intraoperative spinal cord evoked potentials to have a single site of conduction abnormality at the intervertebral level. Twenty-one healthy controls were also evaluated. Motor evoked potentials, compound muscle action potentials, and F wave were recorded from bilateral abductor digiti minimi (ADM) and abductor hallucis (AH) muscles. CMCT was calculated as follows: motor evoked potentials latency − (CMAPs latency + F latency − 1)/2 (ms). Result. The mean values of ADM-CMCT and AH-CMCT at each responsible level were significantly longer than those of normal values (P < 0.01). However, the mean value of ADM-CMCT at the C6–C7 level was markedly shorter than those at the other levels, whereas the mean values of AH-CMCT were not significantly different between each responsible level. We determined that an ADM-CMCT longer than 7.9 ms (mean + 2.5 standard deviation) was abnormal. Using this definition, the sensitivity of ADM-CMCT for CCM was 92% for C3–C4 myelopathy, 95% for C4–C5, 58% for C5–C6, and 9% for C6–C7. Conclusion. ADM-CMCT is useful for the screening of CCM rostral to the C5–C6 level. Diagnosis of patients with C6–C7 myelopathy should include assessment of the AH-CMCT. Level of Evidence: 4